MORPHOLOGICAL AND MOLECULAR CHARACTERIZATION OF Ustilaginoidea virens TIRUPATI ISOLATE CAUSING FALSE SMUT IN RICE (Oryza sativa L.) - K. SRIKANTH (The Journal of Research ANGRAU, 2023)
Rice false smut disease, an emerging threat to rice cultivation worldwide due to its detrimental effects on both grain yield and quality. The study was conducted on characterization of rice false smut fungus viz., U. virens Tirupati isolate in the year 2020-21. It has white coloured fluffy, compact and leathery mycelium with slight undulations and orange or yellowish chlamydospores. The U.virens Tirupati isolate was molecular characterized by sequencing ITS amplicon of 439 bp (GenBank accession number ON987217.1). The phylogenetic analysis revealed that U. virens Tirupati isolate was different from other strains such as MAFF 240994, strain iJS62, strain UV-8b, strain P1, Ustilaginoidea usambarensis and it formed a separate cluster with Ustilaginoidea virens sy1.